Evaluasi Pelaksanaan Praktik Kerja Industri Siswa Kompetensi Keahlian Jasa Boga SMK N 3 Purworejo - Dwi Sapitri Iriani; Soeharto Soeharto (Faculty of Engineering, Universitas Negeri Yogyakarta, 2015)
This study aims to investigate and evaluate: 1) component of context; 2) component of input; 3) component of process; and 4) component of product. The study employed the CIPP model. The research subjects were 65 respondents. The data were collected through a questionnaire, observations, interviews, and documentation. The quantitative data were processed descriptively using SPSS 16.0 program for Windows. The results of the study showed that for context component, there were 34.9% students who strongly agreed, 61.5% who agreed. There were 75% supervising teachers who strongly agreed, 25% who agreed. 100% BS/IS supervisors strongly agreed. The input component, there were 51% students who strongly agreed, 48.8% who agreed. There were supervising 87.5% teachers who strongly agreed, 12.5% who agreed. 100% BS/IS supervisors strongly agreed. The process component, there were 30.2% students who strongly agreed, 48.8% who agreed. There were 62.5% supervising teachers who strongly agreed, 37.5% who agreed. 100% BS/IS supervisors strongly agreed. The product component, there were 41.9% students who strongly agreed, 58.1% who agreed. There were 75.0% supervising teachers who strongly agreed, 25.0% who agreed. 100% BS/IS supervisors strongly agreed. In conclusion, all indicators in each component have been suitable with the implementation of the industrial work practicum in SMK N 3 Purworejo.